2015
DOI: 10.31795/baunsobed.645444
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Çevre Ve Çevre Eği̇ti̇mi̇ İle İlgi̇li̇ Görüşleri̇ Ordu Üni̇versi̇tesi̇ Örneği̇

Abstract: Öğretmen Adaylarının Çevre ve Çevre Eğitimi İle İlgili Görüşleri (Ordu Üniversitesi Örneği) under the title of academic and social sensitivity, and gender and education variables were analyzed according to the department. According to the findings obtained from the study participants results which are achieved by the light the findings; the teacher candidates see the excessive use of natural resources as the most important environmental problem in Turkey and the world, and they said they see environmental orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…However, according to Altın and Oruç (2010), it is stated that the environmental skills included in the program are not few at all. However, since the life studies course curriculum was changed in 2009, 2015, Altın and Oruç (2010 concluded that the environmental outcomes took up a lot of space in these years. However, according to the findings of this study, it can be said that environmental skills occupy less space in the program with the program that changed in 2018.…”
Section: Results and Suggestionmentioning
confidence: 99%
“…However, according to Altın and Oruç (2010), it is stated that the environmental skills included in the program are not few at all. However, since the life studies course curriculum was changed in 2009, 2015, Altın and Oruç (2010 concluded that the environmental outcomes took up a lot of space in these years. However, according to the findings of this study, it can be said that environmental skills occupy less space in the program with the program that changed in 2018.…”
Section: Results and Suggestionmentioning
confidence: 99%
“…Researchers indicate that the awareness of science teachers in particular is quite high regarding ESD. In addition, both teachers and student teachers have positive attitudes towards sustainable development (Demirbaş 2015;Kaya 2013;Kılınç and Aydın 2013;Özgürler and Cansaran 2007;Öztürk 2018;Öztürk and Öztürk 2015;Sağdıç and Şahin 2015;Soysal and Ok 2021;Teksöz et al 2010;Tuncer et al 2006). However, although they are aware of ESD and have positive attitudes towards it, the studies about teacher competencies demonstrate that they do not feel competent enough to teach about ESD (Sagdıç and Şahin 2016;Soysal 2016;Soysal and Ok 2021).…”
Section: Literature Review On Education For Sustainable Development I...mentioning
confidence: 99%
“…Devletlerin, milletlerin, kültürlerin varlığını sürdürebilmesi, doğal çevrenin ve sağlıklı ekosistemin var olmasına bağlı olmakta ve bu nedenle bireylerin bilgi ve sorumluluklarını, yaşamında kalıcı davranış haline getirmesinin sağlanması gerekmektedir. Bu nedenle okul öncesi çağdan başlayarak toplumun her kesimine etkili bir çevre eğitiminin verilmesi önem kazanmaktadır (Atasoy, 2006;Louv, 2005;Öztürk & Öztürk, 2015).…”
Section: Kırsal Ve Kentsel Kesimlerdeki Okul öNcesi çOcuklarının çEvre Kirliliği Hakkındaki Görüşleri Girişunclassified
“…Governments', nations' and cultures' sustaining their existence depends on the existence of the natural environment and the healthy ecosystem and therefore it is necessary to make the knowledge and the responsibilities of the individuals permanent behaviours in their lives. Hence starting from the preschool period it is important to give an effective environmental education to the people from all strata (Atasoy, 2006;Louv, 2012;Öcal, 2013;Öztürk, Öztürk, 2015).…”
Section: Introductionmentioning
confidence: 99%